The Impact of Digital Transformation on the Consumer Experience in Saudi Arabia 2021 - Alkhudairi, Sheikha Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aims to study the impact of digital transformation on the consumer experience and investigate the role of digital transformation in the enhancement of the consumer experience in the Saudi Arabia context. This paper has made an applied attempt in Saudi Arabia to study how digital transformation affects the consumer experience, and what is digital transformation’s role in the enhancement of consumer experience. The research outcomes and results will be discussed at the end of this study. Discussion, implications, conclusion, limitations, and future studies are provided as well.